2013
DOI: 10.4172/2157-7471.1000167
|View full text |Cite
|
Sign up to set email alerts
|

Induction of New Defensin Genes in Tomato Plants via Pathogens-Biocontrol Agent Interaction

Abstract: Defensins and defensin-like peptides are functionally diverse and commonly presented as an immune reaction between plant and pathogen. Trichoderma viride and Bacillus subtilis as biological control agents, were inoculated into the soil, to suppress the activity of the pathogenic fungi Fusarium oxysporum and Rhizoctonia solani on tomato. The up-and down-regulated genes were examined in both treated and non-treated plants, using differential display technique. In treated plants, many up-regulated genes (21) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Basically, most studies demonstrated the important role of JA/ET-induced pathway protecting Trichoderma -treated plants against different pathogens. Systemic defense responses and resistance largely dependent on JA were observed, for example, in A. thaliana protected by Trichoderma against Botrytis cinerea (Contreras-Cornejo et al., 2011) and in tomato plants protected by Trichoderma viride against F. oxysporum or R. solani (Hafez et al., 2013), while Trichoderma -induced resistance in A. thaliana roots based on JA and ET signaling effectively protected them against P. syringae pv. lachrymans (Mathys et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Basically, most studies demonstrated the important role of JA/ET-induced pathway protecting Trichoderma -treated plants against different pathogens. Systemic defense responses and resistance largely dependent on JA were observed, for example, in A. thaliana protected by Trichoderma against Botrytis cinerea (Contreras-Cornejo et al., 2011) and in tomato plants protected by Trichoderma viride against F. oxysporum or R. solani (Hafez et al., 2013), while Trichoderma -induced resistance in A. thaliana roots based on JA and ET signaling effectively protected them against P. syringae pv. lachrymans (Mathys et al., 2012).…”
Section: Discussionmentioning
confidence: 99%